Glocalization: Religion and Science Around the World - Drees, Willem B. (Zygon, 2015)
This essay explains the rationale behind a series of reviews on interactions between knowledge and values, science and religion, in different countries or regions around the world. The series will run in Zygon for the whole of 2015 and beyond. In the literature, it may seem that discussions in the United States and to a lesser extent the United Kingdom are typical of the issues, but they need not be. David Livingstone showed that the reception of evolution differed, even among Calvinists in different countries. Thus, rather than an export model, we should take time to learn from scholars rooted in different contexts how in their situation issues on knowledge and values arise and are dealt with. In this interplay of global processes and local contexts, indicated with the term glocalization, we should be alert to the migration of concepts and the transformations that ideas undergo.